Evaluation of the Response to Breast Cancer Neoadjuvant Chemotherapy Using 18F-FDG Positron Emission Mammography Compared With Whole-Body 18F-FDG PET: A Prospective Observational Study. (March 2017) - Noritake, Mutsumi; Narui, Kazutaka; Kaneta, Tomohiro; Sugae, Sadatoshi; Sakamaki, Kentaro; Inoue, Tomio; Ishikawa, Takashi
Abstract : Purpose: The aim of this study was to assess therapeutic response to breast cancer neoadjuvant chemotherapy (NAC) by 18 F-FDG positron emission mammography (PEM) compared with that to whole-body 18 F-FDG PET (WBPET). Methods: Twenty patients underwent WBPET and PEM 3 times: the first time was before NAC, the second time was after 2 courses of NAC, and the third time was after all courses of NAC. A pathological complete response (pCR) was defined as no evidence of residual invasive cancer with or without ductal carcinoma in situ. The relationships between each modality's SUVmax and pathological response were evaluated. Results: Nine patients achieved a pCR, whereas the other 11 patients had a non-pCR. The SUVmax of WBPET after 2 courses of NAC was significantly lower in the pCR group than in the non-pCR group (1.4 ± 0.4 vs 2.7 ± 2.1, P = 0.0334). There were no significant differences in the SUVmax of PEM (ie, PEM uptake value [PUV]) between the groups. The SUVmax of WBPET (area under the ROC curve [AUC] = 0.761) was superior to the PUVmax (AUC, 0.648) for predicting non-pCR at the interim time point. After all courses of chemotherapy, there were no significant differences between the groups in the SUVmax of WBPET; however, PUVmax was significantly lower in the pCR group than in the non-pCR group (1.0 ± 0.2 vs 2.5 ± 2.7, P = 0.0351). After NAC, the PUVmax (AUC, 0.796) was superior to the SUVmax of WBPET (AUC, 0.671). Conclusions: There proved to be no apparent superiority of PEM in predicting pCR at the interim time point. Positron emission mammography had greater diagnostic capability for detecting residual cancer after all courses of NAC.